The Distribution And Habitat Profiles Of Anaphalis Spp. Outside Protected Forest In Poncokusumo District, Malang Regency - Oo, Tin Naing; Hakim, Prof. Luchman; Afandhi, Aminudin (IJOSMAS, 2022)
The aims of the research were to Identify the species of Anaphalis found in Poncokusumo District, profiling distribution of Anaphalis in Poncokusumo Distrit, and describing habitat of Anaphalis in Poncokusumo District. The benefit of this research is the availability of baseline data as a reference for enforcement of conservation measures for Anaphalis species found in Poncokusumo. Conservation steps that can be taken include socialization of the local community, habitat protection and population monitoring. The field survey was carried out in October-December 2020 by measuring several plots in the area found by Anaphalis. Each site was analyzed for vegetation by measuring the density, frequency and cover of plants. Plant species included in the quadratic plot of 1x1 m2 were identified. In addition, microclimate factors were recorded, such as temperature, humidity and light intensity as well as altitude, coordinate points, soil type and land slope. Interviews with the local people, We interviewed informant especially was key person around we found Anaphalis habitat. We conducted a face-to-face semistructured questionnaire and asked our informants to ask about the distribution, uses and functions, and community conservation efforts of Anaphalis. Data analysis, Vegetation analysis to know composition of plant species inside quadrates for determining diversity index, important value index, dominance and everlasting of plant. Abiotic factors that have been measured are shown in tabular form as a comparison between distribution locations. Information from interview with local person was interpreted qualitatively descriptive. Some of the conservation opportunities in the strategy are policy support for biological conservation and the ecotourism movement, threat aspects such as reduced control of land functions in mass tourism. In this study, the SWOT analysis provides recommendations on significant strategies that come from a combination of strengths and optimizing opportunities, and reducing weaknesses and optimizing opportunities so that strengths reduce threats and manage risks.